Post a New Question

college calculus

posted by .

how do you integrate

sqrt( x^2 - (x^2)(e^(-2x)) )?

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Integral calculus

    Please do help solve the followings 1) Integrate e^4 dx 2) Integrate dx/sqrt(90^2-4x^2) 3) Integrate (e^x+x)^2(e^x+1) dx 4) Integrate xe^x2 dx e^4 is a constant. 3) let u= e^x + x du= (e^x + 1)dx 4) let u= x du=dx v= e^x dv= e^x dx
  2. Math/Calculus #2

    Integrate: 1/(x-sqrt(x+2) dx I came up with: (2/3)(2*ln((sqrt(x+2))-2)+ln((sqrt(x+2))-1)) but it keeps coming back the wrong answer even though I integrated correctly. Is there a way to simplify this answer, and if so, how?
  3. Calculus

    Please look at my work below: Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 +/- Sqrt(2)*i, alpha=8, Beta=Sqrt(2) y(0)=2, e^(8*0)*(c1*cos(0)+c2*sin(0))=c2=2 …
  4. Calculus

    Calc length of arc of y=ln(x) from x=1 to x=2 ---- So far: Definite Integral over x=(1,2) of sqrt(1 + 1/x) dx 1/x = tan^2 t x = 1/tan^2 t sqrt(1+1/x) = sqrt(1+tan^2 t) = sec t dx = -2 * tan^-3 t * sec^2 t dt Integrate over x=(1,2): …
  5. college calculus

    evaulate an intergral for length of curve with y=(sqrt(4-x^2)) and 0 <_ x <_ 2 im lost, i think i know how to apply the formula but its so difficult to integrate and i need to show all my work!
  6. calculus

    Integrate sqrt(x^2 + 1) dx over [0,2*pi] I can substitute u=arctan x to get: Integrate (sec u)^3 du over [0,arctan(2*pi)] From there, I'm stuck. (thanks Count Iblis for your last help)
  7. Calculus

    Integrate: Indefinite integral of [(sqrt(x))-1]^2 / [sqrt(x)] dx
  8. Calculus

    How do I integrate sqrt of (1+e^(2x)) if doing u-sub.. u=sqrt of (1+e^(2x)) and ten using partial fraction...?
  9. Calculus

    Integrate sqrt(16+x^2) dx
  10. Calculus - Integrating

    Question: ∫(x^2)/sqrt(x^2+1) u=x^2+1 , x^2= u-1, du=2xdx ∫(u-1)/sqrt(u) , expand ∫u/sqrt(u) - 1/sqrt(u) Integrate: 2/3(u^(3/2)) - 2u^(1/2) + c My answer: [ 2/3(x^2+1)^(3/2) - 2(x^2+1) + c ] When I took the derivative of this …

More Similar Questions

Post a New Question